The Israeli-Palestinian Conflict through an Integrated Framework of Neorealism and Neoclassical Realism (International relations and international law Journal, 2025)
This article explains why the Israeli-Palestinian conflict persists despite intense international attention in the face of immense human suffering and repeated diplomatic efforts. It aims to provide an explanatory framework that links system-level pressures to domestic politics on both sides. Guided by Neorealism and Neoclassical Realism, the hypothesis is that power asymmetry, great-power positions, and regional mediation are filtered through domestic coalitions, state capacity, security-sector incentives, ideology, and leadership perceptions to produce a four-dimensional deadlock (Israeli, Palestinian, regional, international) that repeatedly narrows the bargaining space. Methodologically, the paper uses a qualitative, comparative case study across major turning points (1948, 1967, 1973/ Camp David, Oslo, 2006-2007, Gaza wars 2008-2021, and 2023-2025). The main result is a consistent mechanism: external pressures set the stage, but domestic filters determine choices, sustaining territorial ‘faits accomplis’ on the Israeli side and irregular tactics plus international appeals on the Palestinian side, while regional actors contain crises and U.S. support limits multilateral leverage. The contribution is theoretical and integrative: it unifies fragmented findings into a single explanatory framework that is tenable across time and escalation levels. Concerning policy-making, the article points to linked policy packages that work simultaneously on systemic incentives and domestic veto players to expand the bargaining space.Keywords: Israeli-Palestinian conflict, neoclassical realism, neorealism, power asymmetry, negotiation deadlock.